Implementing Privacy-Preserving Record Linkage in a Cloud Computing Environment - Brown, Adrian Paul (Curtin University, 2021)
Increased demand for record linkage of administrative data, coupled with privacy risks, presents considerable challenges for many organisations. The primary objective of this research was to develop an operational cloud model for privacy-preserving record linkage utilising scalable computing infrastructure. The thesis presents and evaluates a cloud model for record linkage that links records without sharing personally identifying information, incorporating new techniques for improving accuracy, privacy and performance.